If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -7i = 0 Solving 6 + -7i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -7i = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -7i = 0 + -6 -7i = 0 + -6 Combine like terms: 0 + -6 = -6 -7i = -6 Divide each side by '-7'. i = 0.8571428571 Simplifying i = 0.8571428571
| x^3+4x=7 | | t-8=4w-2 | | 3x+3(-3x-9)=-9 | | 1/3(6x-4)=12 | | 2(x-5)-3(3-x)=.5(x+2) | | 28(28+2x)=1680 | | p-3^1/6=-2^1/2 | | 5m+7-2m-1=9m | | 4x+3=4x-7 | | 2*2*2-4= | | (Y-3)(3y-4)=0 | | 3x^2-2x^2= | | t^2+10t=-4 | | 1/2x2=b | | -32*x*x+120*120*x-80*120*120=0 | | 28(28+28)=1680 | | 6a^2+30= | | 3m-10= | | x^3+9x^2-4x-36=0 | | x-10+x+2=180 | | A=(2-n)180 | | 3.8+5.2-6.7=11.3 | | 45=9(x-5) | | 8xb=5 | | -2r=2 | | 4p-2c+2p=8c | | 36t^2+162t+16=0 | | -5p=-20 | | 6xb=3 | | (x-80)(7x+5)=0 | | 3x^2+3y^2-24x+12y-15=0 | | 4x+3y-9(6x-5y)= |